PEDAGOGICAL CONDITIONS FOR ACTIVATING SELF-EDUCATION OF FUTURE PROFESSIONAL SCHOOL TEACHERS - Vnukova, Olga; Domashenko, Daria; Bobko, Anna (Professional Pedagogics, 2020)
Rålevance: upbringing in the vocational education system is often associated with re-educating or eliminating pre-existing deformities in student behavior. It is a reason, why the teacher of a vocational school is required to be able not only to provide educational services, but also to be a subject of organization of their own lives and their students. The solution of these issues can be found through the formation of self-educational activity of future teachers of a vocational school, mastering their self-education methods. For this purpose is important to create appropriate pedagogical conditions in the institution of higher education.Purpose: to identify and scientifically substantiate the pedagogical conditions for intensifying self-education of future teachers of vocational education.Methods: generalization of literature on the problem, study of pedagogical experience, analysis of vocational education programs for masters and bachelors in vocational education, syllabuses and training programs of educational components for ascertaining competences, learning outcomes and methods of self-education, questionnaires, conversations, oral examination future vocational school teachers and their attitude to the pedagogical conditions of activation of this process.Results: the scientific substantiation of pedagogical conditions of activation of professional self-education of future teachers of vocational school is outlined. Such conditions are presented as specific aspects of the implementation of the educational process and pedagogical activities that contribute to the activation of students' self-education.Conclusions: effective preparation of future teachers of a vocational school is impossible without professional self-education, awareness of the importance and necessity of this process by students and creation pedagogical conditions for its activation. Among them, the most effective are using of educational disciplines and practices to form students' competencies for self-education, strengthening the work of academic group curators to assist students in the preparation and implementation of the self-education program.
Keywords: personality self-education; self-awareness; professional self-education; future teachers of vocational education; pedagogical conditions for activation of self-education